Feasibility of a Mobile Cognitive Intervention in Childhood Absence Epilepsy - Glynn, Peter; Eom, Soyong; Zelko, Frank; Koh, Sookyong (Frontiers in Human Neuroscience, 2016)
Children with childhood absence epilepsy (CAE) frequently present with cognitive comorbidities and school performance concerns. The present study evaluated the feasibility of an intervention for such comorbidities using a mobile cognitive therapy application on an iPad. Eight children with CAE and school concerns aged 7-11 participated in a four-week intervention. They were asked to use the application for 80 minutes per week (20 minutes/day, 4 times/week). Parents and children completed satisfaction surveys regarding the application. Participants were evaluated before and after the intervention using the Cognitive Domain of the NIH Toolbox and by parental completion of the Behavioral Rating Inventory of Executive Function (BRIEF). All eight patients completed the study, using the iPad for an average of 78 minutes/week. Children and parents reported high satisfaction with the application. Though a demonstration of efficacy was not the focus of the study, performance improvements were noted on a processing speed task and on a measure of fluid intelligence. An iPad based cognitive therapy was found to be a feasible intervention for children with CAE.